2012
DOI: 10.1007/s00253-012-4342-3
|View full text |Cite
|
Sign up to set email alerts
|

A novel method for RNA extraction from Andosols using casein and its application to amoA gene expression study in soil

Abstract: The lack of a universal method to extract RNA from soil hinders the progress of studies related to nitrification in soil, which is an important step in the nitrogen cycle. It is particularly difficult to extract RNA from certain types of soils such as Andosols (volcanic ash soils), which is the dominant agricultural soil in Japan, because of RNA adsorption by soil. To obtain RNA from these challenging soils to study the bacteria involved in nitrification, we developed a soil RNA extraction method for gene expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Various types of soil have different characteristics in terms of RNA adsorption (Wang et al ., ). Thus, in a preliminary experiment, we performed RNA extraction from soil using a lysis buffer containing different quantities of casein to investigate the optimal concentration of casein in the lysis buffer as described in a previous report (Wang et al ., ). We found that RNA adsorption by a Fluvisol, which was used in the current experiment, could be ignored so that casein was not necessary for RNA extraction from this soil.…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…Various types of soil have different characteristics in terms of RNA adsorption (Wang et al ., ). Thus, in a preliminary experiment, we performed RNA extraction from soil using a lysis buffer containing different quantities of casein to investigate the optimal concentration of casein in the lysis buffer as described in a previous report (Wang et al ., ). We found that RNA adsorption by a Fluvisol, which was used in the current experiment, could be ignored so that casein was not necessary for RNA extraction from this soil.…”
Section: Methodsmentioning
confidence: 97%
“…We found that RNA adsorption by a Fluvisol, which was used in the current experiment, could be ignored so that casein was not necessary for RNA extraction from this soil. To facilitate RNA extraction from the small amount of soil, RNA was extracted from the RNAlater ® ‐ICE‐treated soil using a ZR Soil/Fecal RNA MicroPrep™ kit (Zymo Research) with modifications, according to a published method (Wang et al ., , ). Briefly, 0.4 g of soil amended with 0.8 mL Na 2 HPO 4 /NaH 2 PO 4 buffer (300 mM, pH 7) was subjected to bead beating at 5.5 m s −1 for 30 s in a FastPrep ® FP120 machine (Qbiogene).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA and RNA were co-extracted from 0.5 g of soil using the method described by Griffiths et al (2000), modified with the addition of casein to increase the nucleic acid yield, as demonstrated by Wang et al (2012). To remove remaining PCR inhibitors, the OneStep PCR inhibitor removal kit (Zymo Research, Irvine, CA, USA) was employed.…”
Section: Methodsmentioning
confidence: 99%
“…In environmental microbiology it is an invaluable approach to further link microbial activity, via gene expression, to microbial and ecosystem processes, compared to DNA approaches alone (Smith and Osborn, 2009;Saleh-Lakha et al, 2011;Gadkar and Filion, 2013). As a result the approach has been used to quantify transcripts to distinguish different pathways of the nitrogen cycle in sediments (Santoro et al, 2010;Smith et al, 2007;Zheng et al, 2013;Damashek et al, 2015;Duff et al, 2017;Santos et al, 2018;Zhang et al, 2018), soil (Leininger et al, 2006;Graham et al, 2011;Wang et al, 2012;Li et al, 2017;Pierre et al, 2017), water column (Tolar et al, 2016;Santoro et al, 2010;Kapoor et al, 2015;Posman et al, 2017;Feng et al, 2018;Gonçalves et al, 2018;Liu et al, 2018;Christiansen et al, 2019) and other microbial processes including water treatment (Gadkar and Filion, 2013;Botes et al, 2013;Wang et al, 2016;Pelissari et al, 2017Pelissari et al, , 2018 and bioremediation (Gadkar and Filion, 2013;Marzorati et al, 2010;Yergeau et al, 2009). In addition to this, cDNA from mRNA or rRNA can undergo PCR for amplicon sequencing to reveal actively transcribing organisms within the environment (Cholet et al, 2019;Zhang et al, 2018;Duff et al, 2017).…”
Section: Introductionmentioning
confidence: 99%